2020
DOI: 10.1186/s12935-020-01652-7
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ST7-AS1, by regulating miR-181b-5p/KPNA4 axis, promotes the malignancy of lung adenocarcinoma

Abstract: Background Growing evidence suggests that suppressor of tumorigenicity 7 antisense RNA 1 (ST7-AS1) is an oncogenic long noncoding RNA (lncRNA). However, little is known on its clinical significance, biological functions, or molecular mechanisms in lung adenocarcinoma (LUAD). Methods The expression of ST7-AS1 and miR-181b-5p were examined by qRT-PCR. The correlations between ST7-AS1 level and different clinicopathological features were analysed. In vitro, LUAD cells were examined for cell viability, migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…On the other hand, TUG1 also decreased the luciferase activity in miR-29c-3p-WT-expressing cells, but not in mutant miR-29c-3p-expressing cells ( Fig 3B ). Furthermore, RIP assay revealed the presence of both TUG1 and miR-29c-3p in the same complex as Ago2, the catalytic component in the RNA-induced silencing complex[ 25 ] ( S3B Fig ). Then miR-29c-3p was predicted to interact with SIRT1 ( Fig 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, TUG1 also decreased the luciferase activity in miR-29c-3p-WT-expressing cells, but not in mutant miR-29c-3p-expressing cells ( Fig 3B ). Furthermore, RIP assay revealed the presence of both TUG1 and miR-29c-3p in the same complex as Ago2, the catalytic component in the RNA-induced silencing complex[ 25 ] ( S3B Fig ). Then miR-29c-3p was predicted to interact with SIRT1 ( Fig 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the role of ST7-AS1 in tumors is mainly to promote tumor progression. The lncRNA ST7-AS1 promotes malignancy in lung adenocarcinoma by regulating the miR-181b-5p/KPNA4 axis (24). The lncRNA ST7-AS1 promotes TRPM7 expression by upregulating microRNA-543 thereby promoting cervical cancer progression (25).…”
Section: Discussionmentioning
confidence: 99%
“…KPNA7 promotes cell growth and anchorage-independent growth, and reduces autophagy of pancreatic cancer cells ( Laurila et al, 2014 ). Previous studies have reported overexpression of KPNA4 in LUAD and identified it as a potential key driver of the malignant phenotype ( Hu et al, 2020 ). Nonetheless, the functional role and underlying mechanism of the KPNA family in LUAD are poorly understood.…”
Section: Introductionmentioning
confidence: 99%